Low-Cost Voltage Zero-Crossing Detector for AC-Grid Applications - Vorobyov Maxim; Vitols Kristaps (Electrical, Control and Communication Engineering, 2014)
Renewable energy sources and energy storage devices are becoming more popular. Some of them like small hydropower turbines, wind turbines and diesel generators produce AC voltage with different frequency and voltage than the main grid. For them power electronics converters are necessary. Power electronics converters presented in industry use two or three level energy conversion, although direct AC to AC converters exist, but one of the main problems is the switch commutation when current or voltage is crossing the zero point. Zero crossing sensors are used to solve this problem. They consist of current or voltage measurement unit and zero crossing detector. Different approaches are used for zero crossing: hardware or software. Hardware approach is simple but it has low precision. Software approach has high precision but it is complicated and expensive. In this paper a simple low cost high precision approach is presented. It takes all advantages from both approaches. While tested with two types of microcontrollers the precision of experimental measurement is 25 μs - 40 μs.